2017
DOI: 10.4067/s0718-95162017005000021
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and distribution of cadmium of three maize hybrids in three environments

Abstract: Anthropogenic soil contamination with heavy metals has received much attention in recent years, especially cadmium (Cd), which is a very toxic element for human health and is exposure is mainly through contaminated food. Maize (Zea mays L.) is one of the most important cereals in the human diet that is characterized as species whose cultivars differ in Cd accumulation. Therefore, identifying and selecting low Cd-accumulating genetic material will contribute to reducing its ingestion. Among the agricultural cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…When the concentration of cadmium reaches 0.2 mg kg −1 , the content values of cadmium in the root, stem, and leaf are 2.14 mg kg −1 , 0.48 mg kg −1 , and 0.27 mg kg −1 , respectively (data not shown). These results were consistent with those of Retamal-Salgado and Shakeel [42,43]. In this scenario, the content of cadmium in the stems was close to the threshold of the cadmium content in feed (0.5 mg kg −1 ) (Table 1).…”
Section: Cadmium Accumulation In M Sativa and Z Mayssupporting
confidence: 91%
“…When the concentration of cadmium reaches 0.2 mg kg −1 , the content values of cadmium in the root, stem, and leaf are 2.14 mg kg −1 , 0.48 mg kg −1 , and 0.27 mg kg −1 , respectively (data not shown). These results were consistent with those of Retamal-Salgado and Shakeel [42,43]. In this scenario, the content of cadmium in the stems was close to the threshold of the cadmium content in feed (0.5 mg kg −1 ) (Table 1).…”
Section: Cadmium Accumulation In M Sativa and Z Mayssupporting
confidence: 91%
“…These radioactive isotopes had varied mobility in the phloem, according to the researchers. Confirmed that phloem transport provided the metal micronutrients Mn, Zn, Co, and Fe and that this transport was linked to the availability of nicotianamine [107]. In addition to its role in long-distance transport, found that nicotianamine is critical for the regulation of metal transfer within cells [108].…”
Section: Discussionmentioning
confidence: 76%
“…Concerning the three oil fields, Saltpond oil field on the average recorded greater number of toxic metals as compared to Jubilee and TEN oil fields. The greater number of heavy metals in crude petroleum recorded suggests that crude petroleum spillage and waste from Saltpond oil field may cause greater ecological imbalance to lives than that from Jubilee and TEN oil fields [1,10,12,38]. However, for the four crude petroleum samples used for the study, metal elements in traces that are biologically toxic to the environment were relatively low in concentrations [1].…”
Section: Resultsmentioning
confidence: 99%